Optimalizace a zefektivnění personálních procesů ve společnosti IT/Telco - Tučková, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Tato práce je zaměřena na oblast lidských zdrojů, konkrétně na optimalizaci a zefektivnění interních personálních procesů ve společnosti IT/Telco, a to pomocí souboru ukazatelů Human Resource Scorecard. Teoretická část definuje termíny, jakými jsou například balanced scorecard, human resource scorecard a benchmarking. Dále popisuje jednotlivé ukazatele a jejich vzorce. Praktická část uvádí výpočty ukazatelů za čtvrtletí let 2008 a 2009, jejich zhodnocení, vývoj a interní benchmarking a navrhuje řešení na zlepšení procesů v dané oblasti.

This diploma thesis is focused on a section of human resource management especially on optimization and efficiency improvement of internal human resource processes in IT/Telco Company using Human Resource Scorecard ratio set. The theoretical part clarifies the terms such as balanced scorecard, human resource scorecard and benchmarking. Then the individual metrics and their formulas are described. The practical part states ratio calculations for the quarters of years 2008 and 2009, their evaluation, development and internal benchmarking and suggests solution to process improvement in given area.
Optimization and Efficiency Improvement of Internal HR Processes in IT/Telco Company.
Keywords: Balanced Scorecard; Human Resource Scorecard; Benchmarking; Balanced Scorecard; Human Resource Scorecard; Benchmarking